Social network correlates of free and purchased insecticide-treated bed nets in rural Uganda - Takada, Sae; Krezanoski, Paul J.; Nyakato, Viola; Bátwala, Vincent; O’Malley, A. James; Perkins, Jessica M.; Tsai, Alexander C.; Bangsberg, David R.; Christakis, Nicholas A.; Nishi, Akihiro (Malaria journal, 2022)
Background: Malaria is a major cause of mortality and morbidity in Uganda. Despite Uganda’s efforts to distribute bed nets, only half of households have achieved the World Health Organization (WHO) Universal Coverage Criteria (one bed net for every two household members). The role of peer influence on bed net ownership remains underexplored. Data on the complete social network of households were collected in a rural parish in southwestern Uganda to estimate the association between household bed net ownership and peer household bed net ownership. Methods: Data on household socio-demographics, bed net ownership, and social networks were collected from all households across one parish in southwestern Uganda. Bed nets were categorized as either purchased or free. Purchased and free bed net ownership ratios were calculated based on the WHO Universal Coverage Criteria. Using network name generators and complete census of parish residents, the complete social network of households in the parish was generated. Linear regression models that account for network autocorrelation were fitted to estimate the association between households’ bed net ownership ratios and bed net ownership ratios of network peer households, adjusting for socio-demographics and network centrality. Results: One thousand seven hundred forty-seven respondents were interviewed, accounting for 716 households. The median number of peer households to which a household was directly connected was 7. Eighty-six percent of households owned at least one bed net, and 41% of households met the WHO Universal Coverage Criterion. The median bed net ownership ratios were 0.67 for all bed nets, 0.33 for free bed nets, and 0.20 for purchased bed nets. In adjusted multivariable models, purchased bed net ownership ratio was associated with average household wealth among peer households (b = 0.06, 95% CI 0.03, 0.10), but not associated with average purchased bed net ownership ratio of peer households. Free bed net ownership ratio was associated with the number of children under 5 (b = 0.08, 95% CI 0.05, 0.10) and average free bed net ownership ratios of peer households (b = 0.66, 95% CI 0.46, 0.85). Conclusions: Household bed net ownership was associated with bed net ownership of peer households for free bed nets, but not for purchased bed nets. The findings suggest that public health interventions may consider leveraging social networks as tools for dissemination, particularly for bed nets that are provided free of charge.
Keywords: Malaria; Bed net; Social networks; Uganda; Insecticide-treated bed net (ITN)